Does women's time in domestic work and agriculture affect women's and children's dietary diversity? Evidence from Bangladesh, Nepal, Cambodia, Ghana, and Mozambique - Komatsu, Hitomi; Malapit, Hazel J.; Theis, Sophie (Elsevier, 2018)
There are concerns that increasing women’s engagement in agriculture could negatively affect nutrition by limiting the time available for nutrition-improving reproductive work. However, very few empirical studies provide evidence to support these concerns. This paper examines the relationship between women’s time spent in domestic work and agriculture and women’s and children’s dietary diversity. Using data from Bangladesh, Nepal, Cambodia, Ghana, and Mozambique, we find that women’s domestic work and cooking time are positively correlated with more diverse diets. We also find differential effects depending on asset poverty status. In Mozambique, working long hours in agriculture is negatively associated with women’s dietary diversity score in nonpoor women, but is positively associated with poor women’s dietary diversity and poor children’s minimum acceptable diet. This suggests that agriculture as a source of food and income is particularly important for the asset poor. Our results reveal that women’s time allocation and nutrition responses to agricultural interventions are likely to vary by socioeconomic status and local context.